Plasma levels of increased miR-195-5p correlates with the sFLT-1 levels in preeclampsia - Sandrim, Valeria Cristina [UNESP] (2016)
Although the role of soluble fms-like tyrosine kinase 1 (sFLT-1) in preeclampsia is well-established, the mechanism related to its synthesis remains poorly understood. We evaluated the association among the circulating microRNAs (miRs) and sFLT-1 levels in preeclampsia pregnant women. For this purpose, we measured the plasma sFLT-1 levels in 24 preeclampsia women and selected from these, three subjects with the lowest and three with the highest levels of sFLT-1 in order to screen for potential miRs associated with plasmatic sFLT-1 concentrations using a polymerase chain reaction-array (PCR-array) methodology. From screening results, we found three statistically different expressed miRs with fold change (FC-high/low levels) ≥3.0: miR-195-5p (FC = 5.2 increase in group with high sFLT-1 levels), miR-16-5p (FC = 3.2; increase in group with high sFLT-1 levels), and miR-375 (FC = −3.0; decrease in group with high sFLT-1 levels) which were later validated in all samples (n = 24). To correlate these miRs and plasma sFLT-1 levels, we used two extremes of analysis. In one part, we compared 12 preeclampsia women with the lowest sFLT-1 levels (L-50% group) to 12 with the highest levels (50% H group); and in the second analysis, 6 preeclampsia women (L-25%) from the L group to 6 preeclampsia women from the H group (H-25%). Our results showed increased expression of miR-195-5p in the H group, considering both the analyses with 50%, FC = 2.1 and 25%, FC = 4.2. Regarding other miRs, lack of correlation was found in both analyses (50% and 25%). In conclusion, our data demonstrate an association of higher levels of sFLT-1 with increased expression of miR-195-5p in preeclampsia pregnant women.